ICTV Virus Taxonomy Profile: Hepeviridae 2022 - Purdy, Michael A; Drexler, Jan Felix; Meng, Xiang-Jin; Norder, Heléne; Okamoto, Hiroaki; Van der Poel, Wim H M; Reuter, Gábor; de Souza, William M; Ulrich, Rainer G; Smith, Donald B (Journal of general virology, 2022)
The family Hepeviridae includes enterically transmitted small quasi-enveloped or non-enveloped positive-sense single-stranded RNA viruses infecting mammals and birds (subfamily Orthohepevirinae) or fish (Parahepevirinae). Hepatitis E virus (genus Paslahepevirus) is responsible for self-limiting acute hepatitis in humans; the infection may become chronic in immunocompromised individuals and extrahepatic manifestations have been described. Avian hepatitis E virus (genus Avihepevirus) causes hepatitis-splenomegaly syndrome in chickens. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Hepeviridae, which is available at www.ictv.global/report/hepeviridae.The family Hepeviridae includes enterically transmitted small quasi-enveloped or non-enveloped positive-sense single-stranded RNA viruses infecting mammals and birds (subfamily Orthohepevirinae) or fish (Parahepevirinae). Hepatitis E virus (genus Paslahepevirus) is responsible for self-limiting acute hepatitis in humans; the infection may become chronic in immunocompromised individuals and extrahepatic manifestations have been described. Avian hepatitis E virus (genus Avihepevirus) causes hepatitis-splenomegaly syndrome in chickens. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Hepeviridae, which is available at www.ictv.global/report/hepeviridae.